Comparison of selected anthropometric characteristics between the point guard and shooting guard/small forward (wing) positions of U18 basketball players - Panagiotis Androutsopoulos; Ilias Blantas; Konstantinos Ntouvas; Panagiotis Alexopoulos (International Journal of Basketball Studies, 2023)
The purpose of the study was to record and compare selected anthropometric characteristics between the PG and SG/SF positions in the U18 age category. The sample size consisted of 20 young male basketball players who participated in this study (mean weight 77.7 kg, mean height 1.91.6 cm, mean age 16.6 years). Players were classified according to their positions in PG: (n = 10) and in SG/SF (Wings) (n = 10). As PGs in this study, players were categorized based on whether they performed the task of organizing the game and had the ball in their hands for most of the live time while as Wings were categorized the players who played in the perimeter off-ball positions. The players participated in the Development Program of the Hellenic Basketball Federation. To determine and compare the anthropometric profile of the players, the following anthropometric characteristics were measured at each position: height, weight, body fat percentage, lean body mass and body mass index (BODY MASS INDEX (BMI)). The sample was studied separately for the two different player positions on the field, PGs and SGs/SFs (wings). In the inductive analysis, possible differences between the different positions of the players were examined. Due to limited sample size (N = 20), tests were performed with the non-parametric Mann-Whitney test for two independent samples. This test compares the average values ​​of the ranks (Ranks) between two groups, where the ranks are the position of each measurement in the ordered set of measurements. The main findings of the study suggest that height, weight and lean body mass are the anthropometric characteristics that separate PGs from SGs/SFs (wings), with the latter prevailing in all three aforementioned variables. More specifically, the SGs/SFs (wings) of this study recorded averages of 1.93.8 cm height, 81.4 kg weight, 73.59 kg FFM while the PGs (organizers) recorded averages of 1.89.4 cm height, 75.1 kg weight, 66.27 kg FFM. In the measurements of body fat percentages (%) and body mass index (BODY MASS INDEX (BMI)), no differences were observed between the examined positions.